ANALISIS PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING FINANCING (NPF) DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP PENYALURAN DANA BANK UMUM SYARIAH - Kukuh Firmansyah; Noor, Iswan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to analyze how Third Party Funds (DPK), Non-Performing Financing (NPF) and Capital Adequacy Ratio (CAR) affect the distribution of Islamic Commercial Bank funds listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses a quantitative descriptive method, the sample is 8 companies, and panel data regression analysis was chosen as a way of analyzing the data. Based on the t test, Third Party Funds (TPF), Non Performing Financing (NPF) and Capital Adequacy Ratio (CAR) have a significant effect on the distribution of Syariah Commercial Bank Funds in 2016-2020 partially. The results of the F test show that the variables of Third Party Funds (DPK), Non Performing Financing (NPF) and Capital Adequacy Ratio (CAR) together have a significant effect on the Distribution of Islamic Commercial Bank Funds.